FRI0276 TIME OF DISEASE EVOLUTION AND EFFICACY OF TOCILIZUMAB IN GIANT CELL ARTERITIS. (June 2019) - Calderón-Goercke, Monica; Loricera, J.; Prieto-Peña, D.; Aldasoro, Vicente; Castañeda, Santos; Villa-Blanco, Ignacio; Humbría, Alicia; Moriano, Clara; Romero-Yuste, Susana; Narváez, J.; Gomez-Arango, Catalina; Perez-Pampín, Eva; et al.
Abstract : Background: Tocilizumab (TCZ) has proved to be effective in the management of Giant Cell Arteritis (GCA). Based on results of the GiACTA trial, it has been approved by the FDA and the European Commission for GCA treatment. Nevertheless, almost half of the GiACTA trial patients presented a short time evolution disease. Objectives: Our aim was to evaluate the efficacy of TCZ according the time of disease evolution. Methods: Retrospective, multicenter study of 134 patients with GCA in treatment with TCZ. A comparative study between two groups according to the time from disease diagnosis and TCZ onset was performed. Results: Our study included 134 GCA patients. TABLE 1 summarizes a comparative study between: a) ≤ 6 months of disease evolution, and b) > 6 months of disease evolution. Non-significant difference in baseline characteristics was found. In terms of visual involvement, we observed more patients affected in the first group (≤ 6 months) (p=0.30). Analyzing clinical improvement non-significant difference was seen during follow-up. At TCZ onset, in the group of ≤ 6 months of evolution, the prednisone dose was higher with a mean dose of 31.3±16.5 mg/d vs 17.7±14.2 mg/d (p<0.001), however, a similar reduction of corticosteroids was achieved in both groups after 6 months of follow-up. The incidence of adverse events and severe infections was similar in both groups (p=0.132 and p=0.672 respectively). Conclusion: In this retrospective analysis, our results support the previously reported efficacy and safety profile of TCZ. We can conclude that TCZ can be used in GCA independently the time of disease evolution. References: [1] Calderón-Goercke M. Tocilizumab in giant cell arteritis. Observational, open-label multicenter study of 134 patients in clinical practice. Semin Arthritis Rheum. 2019Jan5. pii: S0049-0172(18)30571-7. Doi: 10.1016/j.semarthrit.2019.01.003. [Epub ahead of print] [2] Salvarani C, Magnani L, Catanoso M, Pipitone N, Versari A, Dardani L, et al. Tocilizumab: a novel therapy for patients with large-vessel vasculitis. Rheumatolgy (Oxford). 2012; 51:151-6. [3] Stone JH, Tuckwell K, Dimonaco S, Klearman M, Aringer M, Blockmans D, et al. Trial of Tocilizumab in Giant-Cell Arteritis. N Engl J Med. 2017; 377:317-28. Disclosure of Interests: Monica Calderón-Goercke: None declared, J. Loricera: None declared, D. Prieto-Peña: None declared, Vicente Aldasoro: None declared, Santos Castañeda Consultant for: Amgen, BMS, Pfizer, Lilly, MSD, Roche, Sanofi, UCB, Ignacio Villa-Blanco: None declared, Alicia Humbría: None declared, Clara Moriano: None declared, Susana Romero-Yuste: None declared, J. Narváez Consultant for: Bristol-Myers Squibb, Catalina Gomez-Arango: None declared, Eva Perez-Pampín: None declared, Rafael Melero: None declared, Elena Becerra-Fernández: None declared, Marcelino Revenga: None declared, Noelia Alvarez-Rivas: None declared, Carles Galisteo: None declared, Francisca Sivera: None declared, Alejandro Olive: None declared, María Álvarez del Buergo: None declared, Luisa Marena Rojas: None declared, Carlos Fernández-López: None declared, Francisco Navarro: None declared, Enrique Raya: None declared, Eva Galindez: None declared, Beatriz Arca: None declared, Roser Solans-Laqué: None declared, Arantxa Conesa: None declared, Cristina Hidalgo: None declared, Carlos Vázquez: None declared, Jose Andrés Román-Ivorra: None declared, Pau Lluch: None declared, Sara Manrique Arija Speakers bureau: ABBvie, MSD, Janssen, Lillly, Roche, Pfyzer, Novartis., Paloma Vela-Casasempere Grant/research support from: UCB, Abbvie, Pfizer, Roche, Bristol-Myer-Squibb (another research, not BIOBADASER related), Consultant for: UCB, Lilly, Pfizer, Roche, Bristol-Myer-Squibb, Speakers bureau: Roche, UCB, MSD, Pfizer, GSK, BMS, Lilly, Eugenio de Miguel: None declared, Carmen Torres-Martín: None declared, Juan Carlos Nieto: None declared, Carmen Ordas-Calvo: None declared, Eva Salgado-Pérez: None declared, Cristina Luna-Gomez: None declared, Francisco J. Toyos Sáenz de Miera: None declared, Nagore Fernández-Llanio: None declared, Antonio García: None declared, Carmen Larena: None declared, Natalia Palmou-Fontana: None declared, Vanesa Calvo-Río: None declared, Carmen González-Vela: None declared, Alfonso Corrales: None declared, María Varela-García: None declared, Elena Aurrecoechea: None declared, Raquel Dos-Santos: None declared, Ángel García-Manzanares: None declared, Norberto Ortego: None declared, Sabela Fernández: None declared, Francisco Ortiz-Sanjuán: None declared, Montserrat Corteguera: None declared, J. Luis Hernández: None declared, Miguel A González-Gay Grant/research support from: Prof. MA Gonzalez-Gay received grants/research supports from Abbvie, MSD, Jansen and Roche., Speakers bureau: Consultation fees/participation in company sponsored speaker's bureau from Pfizer, Lilly, Sobi, Celgene, Novartis, Roche and Sanofi., Ricardo Blanco Grant/research support from: Abbvie, MSD, and Roche, Consultant for: Abbvie, Pfizer, Roche, Bristol-Myers, Janssen, Speakers bureau: Abbvie, Pfizer, Roche, Bristol-Myers, Janssen